EFEKTIFITAS PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENGANALISIS DATA STATISTIKA MELALUI PENGGUNAAN LEMBAR KERJA MAHASISWA - SUSILAWATI, MADE (E-Jurnal Matematika, 2020)
This study aims to improve students' ability to use software in analyzing Statistics data, especially experimental data with the help of Student Worksheets (LKM). This research was conducted at the Mathematics Study Program at the Faculty of Mathematics and Natural Sciences, Udayana University, on students who were taking the Experimental Design course. The design in this study was a one-group pretest-posttest design, by applying Problem Based Learning. The results of the study showed that the majority of students thought that the use of LKM really helped improve students' understanding of the Experimental Design course. This can be seen also from the average posttest score (82.47) which is higher than the average pretest (65.36). The t test also showed that the increase in the mean pretest to posttest was significant with a p value of 0.000 which was smaller than the 5% significance level. This means that the average student posttest score is higher than the average pretest score.